The Effect of Extending Wait-Time on EFL Students’ Use of Repair Strategies - عبد الحميد ناصر; دكرمنجيان فيفيان (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This experimental study aims at examining the effects of extending WT (the pause after a teacher’s question) on the students’ performance, including the effect on their answers as well as their tendency to self-repair without teacher initiation. The study is divided into two phases: WT1 (no manipulation of WT) and WT2 (WT is manipulated). Each phase consists of five English for non-specialists teaching sessions at the Higher Institute of Languages at Tishreen University, with a sample of 33 students. Results show an increase in the number of right answers in WT2 and a decrease in the cases of failure to respond. Students also tend to repair, and especially to self-repair, more in WT2 using a wide range of repair strategies.